ISCHEMIC HEART DISEASE: PATHOLOGY AND AUTOPSY DIAGNOSIS (Journal of Forensic Medicine & Toxicology, 2014)
Ischemic Heart Disease [IHD] is a generic designation for a group of related syndromes resulting from myocardial ischemia-an imbalance between cardiac blood supply (perfusion) and myocardial oxygen demand1. Myocardial infarction is defined by pathology as myocardial cell death due to prolonged ischaemia, which is the result of a perfusion imbalance between supply and demand. Cell death is categorized pathologically as coagulation and/or contraction band necrosis, which usually evolves through oncosis, but can result to a lesser degree from apoptosis.
Keywords: Patients; Ischemic Heart Disease